Полив’яний посуд з городища Дніпровське-2 - Бураков, А.В. (Археологія, 1991)
Публікація присвячена опису маловідомої в Нижньому Побужжі кераміки доби середньовіччя. Знайдені матеріали вказують на економічні та культурні зв’язки жителів Дніпровського поселення з візантійським Херсоном (XIII ст.). В статье дано подробное описание комплекса поливной посуды XIII в., найденной на поселении Днепровское-2 вблизи Ольвии. Впервые эта посуда появляется на Востоке, через Византию попадает в Херсон, который в XII—XIII вв. налаживает свое производство. Из Херсона она широко распространяется по территории нашей страны — от Нижнего Поднепровья и Побужья до Волхова и от Днестра до Дона. The paper presents a detailed description of a complex of the glazed dishes of the 13th century found in the settlement Dneprovskoe-2 near Olbia. For the first time these dishes had appeared in the East, then came to Chersonese through Byzantium. In the 12-I3th centuries Chersonese organized its own production of such dishes. From the Chersonese they spread in the territory of our country—from the lower Dnieper area and Bug area to Volkhov and from Dnestr to Don.